The U.N.'s Latest Moves on Cross‐Border Mediation and Arbitration Practices. Issue 8 (September 2016) - Trent, Beth
Abstract : Editor's note: From June 27 to July 15, the U.N. Commission on International Trade Law, best known as UNCITRAL, held its 49th session at the United Nations. The International Institute for Conflict Prevention and Resolution, which publishes Alternatives, has been active in UNCITRAL's dispute resolution work over the past five years . The CPR Institute was invited to become an official NGO Observer to UNCITRAL Working Group III (Online Dispute Resolution) in Spring 2011. In Fall 2011, the author was invited to serve as a member of the U.S. Delegation to Working Group III, and she has served on the U.S. delegation to the UNCITRAL Commission beginning with the 45 th Session in 2012. Below is an account of the key conflict resolution issues addressed earlier this summer .